The rise of IIUM as a leading choice for Indonesian students - Abdul Razak, Mohd Abbas; Artalim Zaim, Muntaha (Center for Community Development and Education (CCDE), 2025)
Malaysia, Indonesia, and Brunei, as Muslim countries in the Southeast Asian region, have long enjoyed mutual understanding and strong relationships. Among the three, there are many similarities in terms of food, language, culture, Islamic denomination, ethics, and more. Being Muslim-majority countries, their non-Muslim minorities live in total peace and harmony. These nations are also well-respected among other members of ASEAN (Association of Southeast Asian Nations).